Work Environment on Work Discipline - Yhunita, Isna; Yunita, Yunita (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study examines the influence of the work environment on employee work discipline through a literature review. The main focus is to evaluate how elements of the work environment such as physical atmosphere, organizational culture, and social interactions affect the level of discipline. The methodology used is a literature review from various relevant sources. The findings indicate that a positive work environment can improve work discipline by increasing employee satisfaction and motivation. This study also identifies significant environmental factors and provides recommendations for improvement. The results are expected to provide insight into the development of human resource policies and strategies to create a work environment that supports better work discipline.